Mild Benign Paroxysmal Torticollis—A Case Report from Physical Therapy Settings - Anna M. Ohman (Muscles)
Benign paroxysmal torticollis (BPT) is a condition characterized by episodes of alternating head tilt in infants. Mild cases may be mistaken for Congenital Muscular Torticollis, potentially leading to unnecessary treatment. This case report describes an infant with suspected mild BPT who exhibited alternating head tilt and colic but demonstrated normal motor development. The head tilt resolved spontaneously without intervention. Physical therapists should be aware of mild benign paroxysmal torticollis and monitor such cases carefully to differentiate it from other forms of torticollis and to provide reassurance to parents.